Artificial intelligence - an imperative of the digital society - Tacu, Mariana (Studia Universitatis Moldaviae Științe Economice și ale Comunicării, 2024)
Artificial Intelligence (AI), ranging from basic algorithms to advanced systems, is reshaping our way of life and daily activities. It has a direct impact on mass media and communication, altering traditional paradigms and introducing new technological approaches. AI employs sophisticated algorithms to generate various types of media content, adapting to both traditional environments translated into the virtual realm and inherently digital media. Within the European Union, particular attention is given to online security, connectivity, digital skills, digital businesses, and digital public services. The EU’s cyber security strategy, along with data protection and governance laws, contributes to enhancing access to secure information and databases. The way we approach artificial intelligence will shape the future. To contribute to building a resilient Europe, citizens and institutions should benefit from the advantages offered by AI and feel secure.